Cake Application to Increase Students' English Vocabulary Mastery at SMA Bakti Parit Tiga - Sapitri, Dera; Rasuan, Zulfikri Betyar; Pratiwi, Aisyah (EEdJ: English Education Journal, 2025)
This study's goal is to find out if students in Bakti Parit Tiga High School's class XI can increase their vocabulary by using the Cake app using quasi experimental design. This study focused on employing narrative analysis to look at adjectives, nouns, and verbs in written language. The test results were statistically analyzed using t-test. The results of the study revealed that: (1) students in the treatment group that utilized the cake application achieved an average comprehension score of 94.79; (2) the control group achieved an average score of 88.89; and (3) students in the experimental group who used the cake application excelled at vocabulary mastery compared to the control group at a significance level of 0.03. Since, the two-tailed significant level of 0.03 was lower than the computed significance level, and the t-value of 3.058 was more than the t-critical value of 2.005. The alternative hypothesis (Ha) was validated while the null hypothesis (Ho) was not supported. Based on the previously mentioned data, it can be concluded that there was a significant difference in the students' vocabulary levels according to how they used the Cake app for learning.